Relationship Between Anxiety Symptoms and Age-Related Differences in Tic Severity - Lei T; Yang K; Jun J; Hu S; Yang Q; Hong X; Cui Y (Neuropsychiatric Disease and Treatment)
Tianyuan Lei,1,2 Kai Yang,1,2 JinHyun Jun,1,2 Shujin Hu,1,2 Qinghao Yang,1,2 Xu Hong,3 Yonghua Cui1,2 1Department of Psychiatry, Beijing Children’s Hospital, Capital Medical University, National Center for Children’s Health, Beijing, People’s Republic of China; 2Laboratory for Clinical Medicine, Capital Medical University, Beijing, People’s Republic of China; 3Cloud Services Innovation Laboratory, Institute of Intelligent Science and Technology, China Electronics Technology Group Corporation, Beijing, People’s Republic of ChinaCorrespondence: Yonghua Cui; Tianyuan Lei, Email cuiyonghua@bch.com.cn; tianyuanlei@bch.com.cnPurpose: Tic disorders are neurodevelopmental disorders characterized by movements or vocalizations, often accompanied by anxiety symptoms. However, the relationships between tic severity, age, and anxiety symptoms remain unclear. Here, we investigated the association between tic severity and age and examined how anxiety symptoms might influence this relationship.Patients and Methods: Paediatric patients with tic disorders were recruited from the outpatient clinic of the in Department of Psychiatry at Beijing Children’s Hospital, Capital Medical University. The final sample included 372 subjects (77 females, 295 males; mean age = 10.50 ± 2.70 years; age range: 6.33– 15.92 years). Tic severity was assessed using the Yale Global Tic Severity Scale (YGTSS), while anxiety symptoms were measured using the Screen for Child Anxiety Related Emotional Disorders (SCARED).Results: We found a significant positive correlation between both total and subscale anxiety scores and tic severity. Furthermore, anxiety symptoms, particularly separation anxiety, were found to be significantly correlated with age-related differences in tic severity. In the high anxiety group, tic severity increased significantly with age, mirroring the overall trend. Conversely, in the low anxiety group, tic severity remained relatively stable with age.Conclusion: Our findings highlight the role of anxiety in the progression of tic disorders and emphasize the importance of addressing anxiety in the clinical management of children with tic disorders.Keywords: tic disorders, anxiety symptom, development, children and adolescents